A Community Empowerment Paradigm Model for Sustainable Welfare of Shallot Farmers in Sumenep - Wulandari, Nurlaily; Zuhri, Ach.; Amatillah, Holifah (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the influence of Accessibility and External Access, Farmer Capacity Building, and Social and Institutional Participation on Community Empowerment Paradigm and Farmer Welfare, and to test the mediating role of Community Empowerment Paradigm in efforts to improve the welfare of shallot farmers in Sumenep. This study uses a quantitative approach with a survey method on shallot farmers, while data analysis is carried out using the Structural Equation Model (SEM) to test the direct and indirect relationships between variables. The results show that Accessibility and External Access and Farmer Capacity Building have a significant effect on Community Empowerment Paradigm, but only Farmer Capacity Building is proven to have a significant direct effect on Farmer Welfare. Conversely, Accessibility and External Access, Social and Institutional Participation, and Community Empowerment Paradigm do not have a significant effect on farmer welfare. In addition, Community Empowerment Paradigm is unable to mediate the influence of Accessibility and External Access, Farmer Capacity Building, or Social and Institutional Participation on Farmer Welfare. These findings indicate that the community empowerment that occurs is still social and institutional in nature, and has not yet transformed into economic empowerment that has a direct impact on welfare